FACTORS RELATED TO FALLING RISK PREVENTION OF PATIENTS AT RSUD ENCIK MARIYAM DAIK LINGGA IN 2020 - Zurva Ramayana (Universitas Bengkulu, 2020)
The patient's risk of falling is an increased susceptibility to falls that can cause physical harm. Prevention of falling patients is carried out by means of assessment, the use of a yellow bracelet for a high fall risk; as well as conducting regular monitoring and evaluation. External factors that influence the implementation of fall risk prevention are organizational and management factors, work environment, team factors, staff factors, task factors, patient factors, and communication factors. Monitoring results obtained by nurses have provided fall prevention education, there are still bedrails that are not raised and there are high risk patients. From these data it can be concluded that the nurse has carried out the fall risk assessment properly but the implementation of fall prevention has not been optimal and there is a risk of falling patients. The purpose of this study was to determine the factors related to the risk of falling patients by nurses at Encik Mariyam Daik Lingga Hospital in 2019. This study used a descriptive analytical method with a cross sectional approach, the sample selection was carried out by using total sampling technique, the number of samples used was 32 respondents. The results were analyzed by using the chi square test and showed a relationship between factors, namely knowledge, attitudes and motivation of nurses with preventive measures for the risk of falling patients by nurses at RSUDEncik Mariyam Daik Lingga in 2019. Researcher's suggestions are that nurses can further improve knowledge, attitudes and motivation for good performance. especially in providing nursing care in the form of prevention of the risk of falling patients.